Advertisement Remove all ads

# Differentiate the following w.r.t.x: (x2+2)4x2+5 - Mathematics and Statistics

Sum

Differentiate the following w.r.t.x: (x^2 + 2)^4/(sqrt(x^2 + 5)

Advertisement Remove all ads

#### Solution

Let y = (x^2 + 2)^4/(sqrt(x^2 + 5)
Differentiating w.r.t. x, we get
"dy"/"dx" = "d"/"dx"[(x^2 + 2)^4/(sqrt(x^2 + 5))]

= (sqrt(x^2 + 5)."d"/"dx"(x^2 + 2)^4 - (x^2 + 2)^4."d"/"dx"(sqrt(x^2 + 5)))/(sqrt(x^2 + 5))^2

= (sqrt(x^2 + 5) xx 4(x^2 + 2)^3."d"/"dx"(x^2 + 2) - (x^2 + 2)^4 xx 1/(2(sqrt(x^2 + 5)))."d"/"dx"(x^2 + 5))/(x^2 + 5)

= (sqrt(x^2 + 5) xx 4(x^2 + 2)^3.(2x + 0) - (x^2 + 2)^4/(2sqrt(x^2 + 5)) xx (2x + 0))/(x^2 + 5)

= (8x(x^2 + 5)(x^2 + 2)^3 - x(x^2 + 2)^4)/(x^2 + 5)^(3/2)

= (x(x^2 + 2)^3[8(x^2 + 5) - (x^2 + 2)])/(x^2 + 5)^(3/2)

= (x(x^2 + 2)^3(8x^2 + 40 - x^2 - 2))/(x^2 + 5)^(3/2)

= (x(x^2 + 2)^3(7x^2 + 38))/(x^2 + 5)^(3/2).

Is there an error in this question or solution?
Advertisement Remove all ads

#### APPEARS IN

Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications

Forgot password?